Oxygen Isotopic Variations in the Calcium, Aluminum-rich Inclusion–forming Region Recorded by a Single Refractory Inclusion from the CO3.1 Carbonaceous Chondrite Dar al Gani 083 - Samuel Ebert; Kazuhide Nagashima; Alexander N. Krot; Markus Patzek; Addi Bischoff (The Astrophysical Journal, 2024)
Calcium, aluminum-rich inclusions (CAIs) are the oldest solids dated that formed in the solar system. Most CAIs in unmetamorphosed chondritic meteorites (chondrites; petrologic type ≤3.0) have uniform solar-like ^16 O-rich compositions (Δ ^17 O ∼ −24‰) and a high initial ^26 Al/ ^27 Al ratio [( ^26 Al/ ^27 Al) _0 ] of ∼(4–5) × 10 ^−5 , consistent with their origin in a gas of approximately solar composition during a brief (<0.3 Ma) epoch at the earliest stage of our solar system. The nature of O-isotope heterogeneity in CAIs (Δ ^17 O range from ∼−24 up to ∼+5‰) from weakly metamorphosed chondrites (petrologic type >3.0) remains an open issue. This heterogeneity could have recorded fluctuations of O-isotope composition of nebular gas in the CAI-forming region and/or postcrystallization O-isotope exchange of CAI minerals with aqueous fluids on the chondrite parent asteroids. To obtain insights into possible processes resulting in this heterogeneity, we investigated the mineralogy, rare-earth element abundances, and O- and Mg-isotope compositions of a CAI from the CO3.1 chondrite Dar al Gani 083. This concentrically zoned inclusion has a Zn-hercynite core surrounded by layers of (from core to edge) grossite, spinel, melilite, and Al-diopside. The various phases have heterogeneous Δ ^17 O (from core to edge): −2.2 ± 0.6‰, −0.9 ± 2.1‰, −13.7 ± 2.1‰, −2.6 ± 2.3‰, and −22.6 ± 2.1‰, respectively. Magnesium-isotope compositions of grossite, spinel, melilite, and Al-diopside define an undisturbed internal Al–Mg isochron with ( ^26 Al/ ^27 Al) _0 of (2.60 ± 0.29) × 10 ^−6 . We conclude that the variations in Δ ^17 O of spinel and diopside recorded fluctuations in O-isotope composition of nebular gas in the CAI-forming region prior to injection and/or homogenization of ^26 Al at the canonical level. The ^16 O depletion of grossite and melilite resulted from O-isotope exchange with asteroidal fluid, which did not disturb Al–Mg isotope systematics of the CAI primary minerals.